Penggunaaan Model Inquiry Based Learning (IBL) untuk Meningkatkan Kemampuan Berpikir Kritis Matematis : Analisis Bibliometrik - Revina Nadia Safitri; Hasanuddin Hasanuddin (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The purpose of this study is to examine the development of scientific publications related to the use of the Inquiry Based Learning (IBL) model in improving students' mathematical critical thinking skills from 2015 to 2025. This research uses a bibliometric analysis approach with a descriptive approach, where data is collected through searches on Google Scholar and analyzed using the Publish or Perish and VOSviewer applications to identify publication trends, researcher collaboration, and mapping of main topics. From a total of 200 initial documents, 16 articles met the criteria and were analyzed further. The results showed a fluctuating trend in the publication of IBL studies on MVC, with peaks of attention occurring in 2020 and 2022. Network visualization and keyword density show that IBL and MHS topics continue to be an important focus, but face implementation challenges that require further attention. This research is expected to be a reference in designing effective learning strategies to improve critical thinking skills.